A quantitative and qualitative study of exclusive breastfeeding intention by high-risk pregnant women - Saliba Moimaz, Suzely Adas [UNESP]; Ros, Denise de Toledo [UNESP]; Saliba, Tânia Adas [UNESP]; Saliba, Nemre Adas [UNESP] (Abrasco-assoc Brasileira Pos-graduacao & Saude Coletiva, 2020)
The scope of this research was to assess the breastfeeding intention among high-risk pregnant women and related factors. It is a cross-sectional, qualitative and quantitative study, with 1,118 high-risk pregnant women who attended the prenatal care unit at a specialized center of the Unified Health System. The dependent variables were exclusive breastfeeding intention, intended duration and conditions that might interfere with breastfeeding. The Epi Info 7.4.1, Bioestat 5.3 and IRAMUTEQ 0.7.2.0 programs were used for data processing. The results showed that 8.76% of the pregnant women had conditions that could affect lactation. Among the women, 93.83% affirmed having exclusive breastfeeding intention, of which 69.86% intended to breastfeed until the child was six months old, revealing an association with sociodemographic variables (p<0.05). The intended breastfeeding duration was related to the age (p=0.0041), marital status (p=0.0053) and level of education (p=0.0116). The main reasons reported for not providing exclusive breastfeeding were the following: HIV, use of medications, work and lack of information. This research concluded that a small cohort of high-risk pregnant women presented conditions that could interfere with breastfeeding. Most of them intended to breastfeed exclusively for six months.
Keywords: High-risk pregnancy; Breastfeeding; Qualitative Research